Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages makes it compulsory for the employer in a factory engaged on munitions or Government work to arrange for medical supervision, nursing, and first aid services for the workers, when the Chief Inspector of Factories may require it. The number of doctors employed in factories is now increasing — the Ministry of Supply, for example, have 50 whole-timers and many more part-timers. But though no figures are published for private firms, it is known that only a tiny minority employ doctors. The Order by itself is only a first step towards providing an effective industrial medical service. For one thing, it is very loosely worded; like so much of our legislation affecting welfare, canteens and transport, it says that the employer "might" or "may" be ordered to do something, and not that he "must" or "shall" do it. It is up to the trade union organization in the factory, and especially in large works which employ a number of women and young workers, or where dangerous processes are carried out, to approach the Factory inspector with a view to directing the management to appoint a doctor and nursing staff. In smaller factories a part-time doctor can be asked for, whose services may be shared by a number of works. A serious weakness is that the Order still leaves the appointment of a doctor entirely to the management, by whom he is employed, and no special arrangements are made for Government supervision of the way he carries out his duties. This is unsatisfactory because the ordinary management is not in a position to judge the doctor's qualifications for the post, and since doctors are liable to be called up for the Armed Forces but not for industry, it is often the "left-overs" who find their way into factory jobs. More important still, the fact that the doctor is employed by the management, and the workers have no say in his appointment nor control over his work, often leads to a feeling among the workers that the doctor is the management's "yes-man," that he is employed mainly to save the company compensation expenses and to certify men fit for work as soon as possible. This does not make for the co-operation between workers and doctor which is essential for effective factory medical service. The B.M.A. has suggested* there should be a central advisory body, perhaps under the aegis of a Government Department, which would advise and guide employers in making a suitable choice of an industrial medical officer. Some such machinery is *Report of Committee on Industrial Health in Factories, 1941. 32 21/2049